#TITLE_ALTERNATIVE# - MUHAMMAD IHSAN (NIM: 15109044); Pembimbing: Dr. techn. Dudy D. Wijaya, ST. M.Sc.; Dr. Ir. Dina Ang,
Ionospheric bias is one of the factors that affect the quality of GPS observation data. It is often defined as electron density in ionosphere layer, with a cross-sectional of one square meter, commonly referred to as Total Electron Content (TEC). TEC estimation is used not only for correcting the observation data, but also to study thephenomena and condition on ionsphere. One of the factors that must be -considered to estimat is Receiver Code Bias (RCB). In calculating TEC, RCB is often considered to be constant within one month. However, RCB changes every -day. This thesis will prove that RCB is not constant, and the difference can affect -the TEC value. There are several methods to estimate the RCB. In this thesis, the least square method is used for the estimation. After calculating RCB and TEC of the BAKO station in January 2012 (IGS GPS Station), the result of the estimated RCB varies everyday in a month, although the result of daily mean of RCB in a month is nearly similar with the RCB estimated by The International GNSS Services (IGS). To calculate the impact of daily variation of RCB , the TEC is estimated using different RCB value (daily, weekly, and monthly). The difference of TEC value reaches 5.9 TECU.